Profile of stroke patients treated at a community - based rehabilitation centre in a Cape Town health district - A. J. Rhoda; J. A. Hendry (AOSIS, 2003)
Stroke is a leading cause of death and disability in both developed and developing countries. Limited information is available, in South Africa, on the epidemiological profile of stroke survivors requiring rehabilitation. A descriptive study was therefore undertaken to compile, amongst others the demographic and medical profile of stroke patients attending  rehabilitation at a primary health care facility (Bishop Lavis Rehabilitation Centre).  Both medical- and rehabilitation records were reviewed to ensure completeness of information and to minimize missing clinical data bias. Relevant data was  captured on a data capture sheet.  The latter was based on key findings from the literature and developed by the researcher. The mean age of the population of stroke patients studied was 59 years, which is markedly younger than what has been reported globally in the literature. As was expected, hypertension was found to be the most prevalent risk factor. The presence of a combination of risk factors in the  majority of the group (on average, 2.4 risk factors per person) warrants the introduction of aggressive health  education and stroke prevention programmes at this primary health care centre.